PENGEMBANGAN MODEL PEMBELAJARAN MEMBACA DENGAN PELABELAN OBJEK SEKITAR (POS) BAGI MURID TAMAN KANAK-KANAK - Basuki - - (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to develop a reading learning model for kindergarten students. This was a research and development study consisting of four stages, i.e. (1) a preliminary (exploratory) study, (2) model development, (3) model testing, and (4) product dissemination. The results of the study are as follows. First, generally the reading learning quality in kindergartens is not satisfactory and teachers need a reading learning modeleasily applicable and effective to attain objectives. Second, the development of a reading learning model by surrounding object labeling (SOL) is made through a workshop, expert validation, and a small-scale tryout. Third, the reading learning model by SOL is capable of significantly improving kindergarten students’ reading ability in comparisonwith the conventional method. Fourth, Keempat, the reading learning model by SOL has been disseminated to stakeholders in order to understand and be able to implement it at school.